Uji Banding Kualitas Tablet Ketoprofen Generik Dengan Merek Dagang - Maria Dona Octavia; Auzal Halim; Marlani Marlani (STIFARM Padang, 2016)
Ketoprofen is a non steroid Anti Inflamation Drug (NSAID) and most of ketoprofen tablets have been sold in the market are the ones which generic names and branded names. The aim of this research is to compare the quality of ketoprofen tablets 100 mg which are taken from the generic ones and the branded ones, the date were four types of ketoprofen tablets which consist of two types generic tablets and two types of branded tablets. The measurement of ketoprofen tablets quality is based on the quality standard of ketoprofen tablets which refers to The pharmacope Indonesian the fourth editions. The quality parameter of ketoprofen tablets involved similarity test of weight and size, solodity, friability analysis, disintegration time, composition standard test and disolution profile test. Disolution profil test of ketoprofen tablets was ronducted by using paddle method, measured by spectrofotometer UV, and tested by using phosphate buffer power Hidrogen 7.4 as its medium. Then the result was gotten in 60th minutes for each sample. Sample g1 = 94.89%, sample g2 = 97.52%, sample m1= 100.10% and sample m2= 101.08%. Composition standard test of ketoprofen tablets, was conducted by using spectrofotometer UV and tested by using methanol P 75% as its medium. The result of this shows that the quality of sample g1 = 98.92%, sample g2 = 97.02%, sample m1 = 97.97%, m2 = 100,71%. The result of quality parameter test shows that both of generic and branded ketoprofen tablet fullfiks the quality standard of pharmacope Indonesian the fourth editions.